Arguments for Non-adversariality are not Self-refuting - Kiš, Serhij (Springer, 2025)
In his contribution to the adversariality debate, Scott Aikin argues that non-adversarialism about arguments is self-refuting because whenever its proponents affirm it, they inevitably reject adversarialism and thus become adversarial themselves. This, Aikin suggests, follows from the idea that reasons are contrastive—always for one thing instead of another. Here, I defend the non-adversariality project against this self-refutation charge. I do this by identifying one of the core tenets of adversarialism, namely that it views arguments are as zero-sum games. I then argue that Aikin’s self-refutation charge only obtains if we assume that the adversariality debate itself is zero-sum. However, whether the debate is zero-sum depends on how it is framed, and we might as well frame the debate in positive-sum terms. To illustrate, I draw on Katharina Stevens’ virtue-theoretic account, which offers such a positive-sum view by synthesizing insights from both adversarialist and non-adversarialist camps. For Stevens, a virtuous arguer is both adversarial and cooperative, guided by practical wisdom in adopting the most suitable arguing style for a given context. I contend that this approach bypasses Aikin’s challenge by shifting the question from whether arguments are inherently adversarial to when the adversarial or cooperative style is the most appropriate. I conclude by drawing a broader lesson for the adversariality debate, which is that some of the ways in which it is framed might keep our attention from other substantial research questions, such as how to counter the crowding-out of respect in our disagreements and thus mitigate the subsequent political polarization.
Keywords: Adversariality; Argumentation; Contrastivism about reasons; Framing; Virtue theory; Scott Aikin